Fiber Optic Magnetic Field Sensor Based on Magnetic Nanoparticle Assembly in Microcapillary Ring Resonator - Zhe Yu; Junfeng Jiang; Xuezhi Zhang; Kun Liu; Shuang Wang; Wenjie Chen; Tiegen Liu (IEEE Photonics Journal)
A magnetic field sensor based on the magnetic-field-induced nanoparticle assembly effect in microcapillary whispering gallery mode (WGM) ring resonator is proposed and experimentally demonstrated. The chemical characteristics of nanoparticles and the silica microcapillary are used to link up the surface density of the resonator and the magnetic field intensity. The magnetic field variation changes the surface density of nanoparticles adsorbed on the sensor surface and respond to the WGM transmission spectra shift. Because of the powerful surface sensing capability of WGM, the maximum sensing sensitivity reaches 57.59 nm/mT and the detection limit reaches 1.39 × 10 –4, respectively. The magnetic field response characteristic of the sensor is studied as well. This provides the potential to fiber-based magnetic field sensing applications.